Attitudes and awareness of professionally active people on eye diseases prevention—a descriptive cross-sectional survey - Mierczak, Karina; Garus-Pakowska, Anna (Frontiers in Public Health, 2025)
IntroductionThe use of screen devices is a common aspect of everyday life. Additionally, for the majority of adult workers, their job is closely associated with using monitors. Prolonged or improper use of screens, especially at a close distance from the eyes, can result in eye fatigue and the development of basic refractive errors. Professional workers are particularly susceptible to the onset of certain vision disorders, notably those related to prolonged near work and screen exposure (such as myopia), and awareness of potential risks contributes to the mitigation of negative consequences associated with visual impairments.ObjectiveTo assess the level of awareness and attitudes regarding preventive measures for eye diseases among working individuals.Material and methodsA survey was conducted from September 27th, 2023 to December 1st, 2023, among 251 working individuals. The research tool consisted of a custom proprietary survey questionnaire. The obtained survey results were subjected to statistical analysis using non-parametric tests (χ2, Fisher's, Kruskal-Wallis) and parametric tests (Bartlett's, ANOVA), depending on the type of data.ResultsOnly 32.27% of participants demonstrated a satisfactory level, and 30.28% a good level of awareness regarding the prevention of eye diseases. A correlation was found between the level of awareness and education. Individuals with intermediate and higher education most frequently received satisfactory and good evaluations. The highest mean score was 25.55 out of 38 possible points and was achieved by participants with higher education. No significant correlation was observed between the level of awareness and the type of occupation.ConclusionsThe level of awareness and attitudes of the surveyed group of working individuals regarding the prevention of eye diseases is limited. Therefore, it is crucial to strive for a change in the current state and to expand the awareness of working individuals in Poland regarding the safe use of screen devices in both stationary (office) and remote (home) work conditions.